2022
DOI: 10.3390/jof8121296
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Physiological Adaptations of the Xylotrophic Basidiomycetes Fungi to CO2 and O2 Mode in the Woody Habitat

Abstract: The aim of this research is to study of eco-physiological adaptations of xylotrophic fungi (Basidiomycota, Agaricomycetes) to hypoxia, anoxia and hypercapnia as the main environmental factors that determine the activity of fungi in woody habitat. The study was carried out on seven species of polypore fungi widespread in the preforest-steppe pine-birch forests of the Central Urals, including both white (D. tricolor, D. septentrionalis, F. fomentarius, H. rutilans, T. biforme) and brown (F. betulina, F. pinicola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This observation aligns with prior studies indicating that the growth and wood decay activities of saprotrophic fungi diminish when O2 levels fall below 1.5% and 10% or 1%, respectively, and CO2 levels rise accordingly [29,32]. Contrarily, [31] found that xylothrophic basidiomycetes could completely exhaust O2 in their environment and withstand high CO2 levels, even up to 100%. These fungi are, therefore, facultative anaerobes that produce CO2 in O2-deprived environments.…”
Section: Dependence Of Fungal Ch4 Formation On O2 Levelssupporting
confidence: 91%
See 2 more Smart Citations
“…This observation aligns with prior studies indicating that the growth and wood decay activities of saprotrophic fungi diminish when O2 levels fall below 1.5% and 10% or 1%, respectively, and CO2 levels rise accordingly [29,32]. Contrarily, [31] found that xylothrophic basidiomycetes could completely exhaust O2 in their environment and withstand high CO2 levels, even up to 100%. These fungi are, therefore, facultative anaerobes that produce CO2 in O2-deprived environments.…”
Section: Dependence Of Fungal Ch4 Formation On O2 Levelssupporting
confidence: 91%
“…However, the influence of key parameters like O2 availability and temperature on fungal CH4 formation has not been investigated, even though these factors strongly influence the physiological activity and growth of fungi. Studies have shown that the activity and growth of xylothrophic fungi depend on prevailing O2 mixing ratios [29][30][31]. For instance, xylothrophic fungi, which include the two investigated fungi in this study, can consume all available O2 in their woody habitat and still grow under anoxic conditions [31].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the influence of key parameters like O 2 availability and temperature on fungal CH 4 formation has not been investigated, even though these factors strongly influence the physiological activity and growth of fungi. Studies have shown that the activity and growth of xylotrophic fungi depend on prevailing O 2 mixing ratios [29][30][31]. For instance, xylothrophic fungi, which include the two investigated fungi in this study, can consume all available O 2 in their woody habitat and still grow under anoxic conditions [31].…”
Section: Introductionmentioning
confidence: 79%
“…The main role in the decomposition of debris in forests of temperate latitudes is played by xylotrophic fungi − Basidiomycota, Agaricomycetes [7][8][9][10]. This is, perhaps, the only group of organisms in the modern biosphere that has a unique set of interconnected ecological and physiological adaptations to the woody habitat and is capable of decomposing the lignocellulosic complex of wood [11]. They determine the main parameters of CO2 emission activity of woody debris and this makes them one of the globally significant regulators of the gas composition of the atmosphere [12], factors of climate stability and change [5].…”
Section: Introductionmentioning
confidence: 99%